Chocolate protects a heart and vessels - Małgorzata Chudzińska; Jarosław Pietrzak; Magdalena Węglarz; Łukasz Wołowiec; Daniel Rogowicz; Walery Zukow; Władysław Sinkiewicz (Kazimierz Wielki University, 2017)
A healthy diet plays a key role in the prevention and management of cardiovascular diseases. Atherosclerosis and its complications are nowadays one of the leading causes of death in the western population. Among numerous factors known for slowing down the progression of the disease is the consumption of vegetables, fruits and chocolate rich in multiring compounds called polyphenols. Chocolate is a source of catechins, epicatechins and procyanidins. Recently, several studies have demonstrated the beneficial effects of dark chocolate in management of hypertension  by hypotensive effect associated with vasorelaxation mediated most likely by the stimulation of nitric oxide production in the vascular wall. Cocoa and its derivatives have also strong antioxidative properties resulting in enhancement of the  total antioxidant potential and inhibition of lipid peroxidation. It was also demonstrated that cocoa polyphenols have a favourable antithrombotic effect connected with the inhibition of platelet activation. Chocolate may diminish insulin resistance and inhibit inflammatory process. Cocoa improves also psychical well being. This pleiotropic activity of cocoa results in slowing down the progression and limiting the complications of atherosclerosis in regular chocolate consumers.